Ruminant Placental Adaptation in Early Maternal Undernutrition: An Overview - Toschi, Paola; Baratta, Mario (Frontiers in Veterinary Science, 2021)
Correct placental development during early gestation is considered the main determinant of foetal growth in late pregnancy. A reduction in maternal nourishment occurring across the early developmental window has been linked to a wide range of pregnancy disorders affecting placental transport capacity and consequently the foetal nutrient supply line, with long-term implications for offspring health and productivity. In livestock, ruminant species specifically experience maternal undernutrition in extensive systems due to seasonal changes in food availability, with significant economic losses for the farmer in some situations. In this review, we aim to discuss the effects of reduced maternal nutrition during early pregnancy on placental development with a specific focus on ruminant placenta physiology. Different types of placental adaptation strategies were examined, also considering the potential effects on the epigenetic landscape, which is known to undergo extensive reprogramming during early mammalian development. We discussed the involvement of autophagy as a cellular degradation mechanism that may play a key role in the placental response to nutrient deficiency mediated by mammalian target of rapamycin, named the mTOR intracellular pathway